India's strategic culture : the making of national security policy - Paranjpe, Shrikant (New York : Routledge, 2020)
"This book provides a comprehensive understanding of the evolution of India's strategic culture in the era of globalisation. It examines dominant themes that have governed India's foreign and security policy and events which have shaped India's role in global politics. The author Examines the traditional and new approaches to diplomacy and the state's response to internal and external conflicts; Delineates policy pillars which are required to protect the state's strategic interests and forge new relationships in the current geopolitical climate; Compares the domestic and international security policies followed during the tenures of Narsimha Rao, Atal Bihari Vajpayee and Manmohan Singh and; Analyses how the Narendra Modi era has brought on changes in India's security strategy, and the use of soft power and diplomacy. With extensive additions, drawing on recent developments, this edition of the book will be a key text for scholars, teachers and students of defense and strategic studies, international relations, history, political science and South Asian studies"--
OCLC-licensed vendor bibliographic record.
Keywords: National security -- India; POLITICAL SCIENCE / General; SOCIAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General